Search for the Standard Model Higgs boson in the decay channel H -> ZZ((*)) -> 4l with 4.8 fb(-1) of pp collision data at root s=7 TeV with ATLAS - Onofre, A. (2012)
This Letter presents a search for the Standard Model Higgs boson in the decay channel View the MathML sourceH→ZZ(⁎)→ℓ+ℓ−ℓ′+ℓ′−, where ℓ,ℓ′=eℓ,ℓ′=e or μ , using proton–proton collisions at View the MathML sources=7 TeV recorded with the ATLAS detector and corresponding to an integrated luminosity of 4.8 fb−1. The four-lepton invariant mass distribution is compared with Standard Model background expectations to derive upper limits on the cross section of a Standard Model Higgs boson with a mass between 110 GeV and 600 GeV. The mass ranges 134–156 GeV, 182–233 GeV, 256–265 GeV and 268–415 GeV are excluded at the 95% confidence level. The largest upward deviations from the background-only hypothesis are observed for Higgs boson masses of 125 GeV, 244 GeV and 500 GeV with local significances of 2.1, 2.2 and 2.1 standard deviations, respectively. Once the look-elsewhere effect is considered, none of these excesses are significant.